ChemInform Abstract: Reduced Graphene Oxide Supported Piperazine in Aminocatalysis. Issue 44 (4th November 2014) - Rodrigo, Eduardo; Garcia Alcubilla, Beatriz; Sainz, Raquel; Fierro, J. L. Garcia; Ferritto, Rafael; Cid, M. Belen
Abstract The title catalyst is employed in Knoevenagel, Michael and Aldol reactions.